Family mediation in Ireland - Conneely, Sinead Maire (Trinity College (Dublin, Ireland). School of Law, 2001)
Empirical research into the operation of the family mediation service in the Republic of Ireland is set against a backdrop of theoretical and practical discussion. Chapter One analyses the principles and practices of various mediation forms and provides the essential arguments in favour of mediation. Chapter Two outlines the negative view adopted by feminists, the informal justice critics and others while Chapter Three provides an extensive review of the empirical literature surrounding the exercise of mediation in other common law jurisdictions. The central themes of gender, domestic violence, child contact and the interests of children are revisited in each section. Client and mediator questionnaires were randomised, computerised and graphed using the SPSS package in order to illuminate the issues in Chapter Four. Specifically, the project assessed the demographics of clients entering the mediation service, their emotional and material state and the level of conflict in their relationship. Clients were tracked through the system, m order to establish the rate and form of agreement reached, the reasons for any absence of settlement and the future intentions of the couples. Consumer assessment of the mediation experience and the extent to which they considered the experience helpful was logged.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin